Elucidation of signaling molecules involved in ergosterol perception in tobacco - Dadakova, Katerina; Klempova, Jitka; Jendrisakova, Tereza; Lochman, Jan; Kasparovsky, Tomas (Plant physiology and biochemistry, 2013)
Ergosterol, a principal compound of the fungal plasma membrane, is regarded as a pathogen-associated molecular pattern. In the present study, the role of salicylic acid (SA), jasmonic acid (JA) and spermine signaling pathways after ergosterol elicitation were evaluated. SA, JA and spermine production, as well as accumulation of transcripts for a lipoxygenase (NaLOX3) gene, the phenylalanine-ammonia lyase gene, selected pathogenesis-related genes (PR1, PR5), and peroxidase tPOXC1 were determined in tobacco (Nicotiana tabacum L. cv. Xanthi) in response to ergosterol elicitation. To understand the sequence of the signaling cascade, several representative steps involved in the synthesis of crucial signaling molecules were targeted using specific inhibitors. SA signaling pathway, together with calmodulin-dependent protein kinases and nitric oxide, was demonstrated to play an important role in the induction of defense-related genes following ergosterol treatment. The results suggested that nitric oxide participates in defense-related gene activation following ergosterol treatment but does not directly participate in activation of reactive oxygen species production. The induction of PR5 and tPOXC1 transcripts was found to be not fully dependent on calmodulin/Ca2+ and SA signaling, contrary to the PR1a transcript. A possible candidate for this SA-independent pathway is the spermine pathway, as elevated spermine levels were detected following ergosterol treatment.
Keywords: cyklopentany; phenylalanine-ammonia lyase; salicylic acid; Calmodulin; Ergo; nemoci rostlin; cholesterol; kalmodulin; Cyclopentanes; l-NMMA; nitric oxide; nitric oxide synthase; ROS; houby; NOS; oxylipiny; Chole; PR; 4-amino-5-methylamino-2′,7′-difluorofluorescein diacetate; Spermine; NO; reactive oxygen species; N-methyl-l-arginine acetate salt; Plant Proteins; RT-qPCR; odolnost vůči nemocem; Disease Resistance; Nicotiana; phospholipase A(2); tPOXC1; Tobacco; ruthenium red; jasmonic acid; Reactive Oxygen Species; pathogenesis-related; signální transdukce; PAL; vápník; PLA2; real-time quantitative polymerase chain reaction; Signal Transduction; cPTIO; rostlinné proteiny; Oxylipins; Fungi; ergosterol; Signaling; rostlinné geny; Calcium-Calmodulin-Dependent Protein Kinases; Calcium; RR; Salicylic acid; tobacco peroxidase C1; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; Ergosterol; kyselina salicylová; Plant Diseases; JA; N-(6-aminohexyl)-5-chloro-1-naphthalenesulphonamide; Salicylic Acid; reaktivní formy kyslíku; DAF-FM DA; exprese genu; SA; Defense; spermin; proteinkinasy závislé na vápníku a kalmodulinu; oxid dusnatý; tabák; 2-(4-carboxyphenyl-4,4,5,5-tetramethylimidazoline-1-oxyl 3-oxide; Genes, Plant; Nitric Oxide; Gene Expression; W7; Jasmonic acid